Contrasting the risk factors of grief and burden in caregivers of persons with dementia: Multivariate analysis. (19th November 2018) - Liew, Tau Ming; Tai, Bee Choo; Yap, Philip; Koh, Gerald Choon‐Huat
Abstract : Background: Caregivers of persons with dementia (PWD) can experience loss and grief long before the death of the person. While such phenomenon of pre‐death grief (PDG) has been increasingly described, we are uncertain how it can be distinct from the well‐studied construct of caregiver burden. Objective: To determine whether there are differences in the risk factors of PDG and caregiver burden to aid in our understanding of the relationship between the two constructs. Methods: Spouses or children of community‐dwelling PWD were consecutively sampled from two tertiary hospitals. They completed questionnaires containing a PDG scale, a caregiver burden scale, and information related to the caregiver and PWD. Risk factors of PDG and caregiver burden were identified using multivariate regression, within which PDG and caregiver burden scores were jointly included as two separate dependent variables. Results: We recruited 394 caregivers with a mean age of 53.0 years (SD 10.7), majority were Chinese (86.6%), children caregivers (86.3%), and primary caregivers (70.8%). In the regression analyses, we identified three risk factors which were shared by both PDG and caregiver burden (later stage of dementia, behavioral problems in PWD, and primary caregiving role) and three other risk factors which were unique to PDG alone (younger age of PWD, lower educational attainment of caregivers, and spousal caregiver). Conclusions: The different risk factor profiles evidence a distinction between PDG and caregiver burden. They may possibly be distilled into a framework to direct our approach to PDG interventions, which may include using caregiver burden as an opportunity to initiate conversations on grief, exploring the various aspects of losses and encouraging adaptive coping.